Adopting and Challenging Traditional Gender Roles in 90s Sitcom Friends - Clarissa Angelia; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2022)
Sitcom has been worldwide famous since the 1950s. Friends is one of the most well-known sitcoms, telling the story of friends who lived in New York City during their youth. I will analyze gender roles issues in Friends. In this study, I will analyze how the six main characters adopt traditional gender roles and how the six main characters eventually challenge them. I use several theories, such as traits of traditional gender roles, theory of gender roles orientation, and theory of egalitarianism. My analysis demonstrates that each of the six main characters adopted at least one trait of traditional gender roles at the beginning of the series. The traits they adopted will be categorized by their personal attitude, social behavior, value, self-concept, and career choice. By the end of the series, the six main characters had eventually challenged traditional gender roles and adopted more to the Egalitarianism theory.